Mesopore Formation and Silicon Surface Nanostructuration by Metal-Assisted Chemical Etching With Silver Nanoparticles - Pinna, Elisa; Le Gall, Sylvain; Torralba, Encarnacion; Mula, Guido; Cachet-Vivier, Christine; Bastide, Stéphane (Frontiers in Chemistry, 2020)
his article presents a study of Metal-Assisted Chemical Etching (MACE) of silicon in HF-H2O2 using silver nanoparticles as catalysts. Our aim is a better understanding of the process to elaborate new 3D submicrometric surface structures useful for light management. We investigated MACE over the whole range of silicon doping, i.e. p++, p+, p, p-, n, n+ and n++. We discovered that, instead of the well-defined and straight mesopores obtained in p and n-type silicon, in p++ and n++ silicon MACE leads to the formation of cone-shaped macropores filled with porous silicon. We account for the transition between these two pore-formation regimes (straight and cone-shaped pores) by modeling (at equilibrium and under polarization) the Ag/Si/electrolyte (HF) system. The model simulates the system as two nanodiodes in series. We show that delocalized MACE is explained by a large tunnel current contribution for the p-Si/Ag and n-Si/HF diodes under reverse polarization, which increases with the doping level and when the size of the nanocontacts (Ag, HF) decreases. By analogy with the results obtained on heavily doped silicon, we finally present a method to form size-controlled cone-shaped macropores in p silicon with silver nanoparticles. This shape, instead of the usual straight mesopores, is obtained by applying an external anodic polarization during MACE. Two methods are shown to be effective for the control of the macropore cone angle: one by adjusting the potential applied during MACE, the other by changing the H2O2 concentration. Under appropriate etching conditions, the obtained macropores exhibit optical properties (reflectivity ~3 %) similar to that of black silicon.